First-principles Calculations of TlCdF3 Compound under Pressure - Belgin Koçak; Yasemin Çiftci (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
The present study focused on investigating various properties including structural, elastic, electronic, and optical of TlCdF3 compound under hydrostatic pressure using Density Functional Theory (DFT). The estimated results were consistent with previous investigations. The analysis of the electronic band structures between 0 and 50 GPa revealed that this compound possesses an indirect band gap. The stress-strain method was used to explain elastic properties, and the findings revealed that this compound is ductile, anisotropic and mechanically stable between 0 and 50 GPa. Investigations were done on significant optical features such as refractive index n (𝜔), extinction coefficient k (𝜔), absorption coefficient α (𝜔) and reflectivity R (𝜔) at various pressures between 0 and 50 eV. Our results imply that TlCdF3 compound has the potential for a broad range of technological applications under hydrostatic pressure.